(untitled) (Conferencea, 2022)
Most of the production of building materials in the article the basic technological device atagiven rotational speed of the mill one who rida sharli a method to calculate the condition. Sharli calculation methods of the rotational speed of the mill is detected on the basis of scientific studies provide detailed information in the source is illuminated.